2020
DOI: 10.26434/chemrxiv.12279686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Making Hydrogels Stronger through Hydrophilicity-Hydrophobicity Transformation, Thermoresponsive Morphomechanics and Crack Multifurcation

Abstract: <p>The development of mechanically strong, flexible and crack-resistant hydrogels is of great academic and practical significance and demands for the biomimetic exploration of energy dissipation pathways. The rational design of strong hydrogels is also limited by insufficient mechanism study, resulting from the lack of powerful technique to “see” hydrogels at morphological level. Herein, we constructed a thermoresponsive mechanically strong hydrogel from poly(<i>N</i>-isopropylacrylamide) (PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Nellas and coworkers performed a molecular dynamics simulation of pentamer PNIPAM [ 37 ], and they suggest a clathrate-like behavior in the coordinate shell might be responsible for the LCST behavior of PNIPAM. Tang et al directly observed the hydrophilicity–hydrophobicity transformation of PNIPAM by the utilization of aggregation-induced emission luminogens [ 38 ]. In that study, it was found that the hydrophobicity change of PNIPAM chains was due to the formation of multiple interchain/intrachain hydrogen bonds.…”
Section: Thermogelling Mechanism/thermogelling Propertiesmentioning
confidence: 99%
“…Nellas and coworkers performed a molecular dynamics simulation of pentamer PNIPAM [ 37 ], and they suggest a clathrate-like behavior in the coordinate shell might be responsible for the LCST behavior of PNIPAM. Tang et al directly observed the hydrophilicity–hydrophobicity transformation of PNIPAM by the utilization of aggregation-induced emission luminogens [ 38 ]. In that study, it was found that the hydrophobicity change of PNIPAM chains was due to the formation of multiple interchain/intrachain hydrogen bonds.…”
Section: Thermogelling Mechanism/thermogelling Propertiesmentioning
confidence: 99%
“…Adapted with permission. [ 41 ] Copyright 2020, The Authors, preprinted by ChemRxiv. b) Synthetic route to the TPE‐[P(DMA‐ stat ‐DAA)] 2 copolymer and preparation procedure for obtaining hydrogels from the copolymer and PEODH.…”
Section: Fabricationsmentioning
confidence: 99%
“…used PNIPAM‐based 13 as an indicator to visualize the hydrophilicity–hydrophobicity transformation of hydrogels. [ 41 ] PNIPAM is a thermo‐responsive polymer that undergoes a coil‐to‐globule transition from the hydrophilic to the hydrophobic state when the temperature changes across lower critical solution temperature (LCST). Upon heating the obtained GND hydrogels from 20 to 60 °C, the fluorescence of the hydrogels was enhanced, accompanied by a blue‐shift, as shown in Figure a,b.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure a,b, a water‐soluble AIEgen 13 with D−A structure exhibited evident polarity‐dependent emission in different solvents, indicating an obvious TICT character. [ 178 ] To test the polarity of polymer film, 13 was physically doped in PS and chemically incorporated in the poly( N ‐isopropylacrylamide) (PNIPAM) hydrogel, respectively. The PL spectra of 13 in the PNIPAM hydrogel exhibited an obvious blueshift and enhancement when heated from 20 to 60 °C and the corresponding emission color changed from red to blue (Figure 16c).…”
Section: Temperature‐responsive Aiegensmentioning
confidence: 99%